Outbreak investigation of ceftriaxone-resistant Salmonella enterica serotype Typhi and its risk factors among the general population in Hyderabad, Pakistan: a matched case-control study. Issue 12 (December 2018) - Qamar, Farah Naz; Yousafzai, Mohammad Tahir; Khalid, Muhammad; Kazi, Abdul Momin; Lohana, Heeramani; Karim, Sultan; Khan, Ayub; Hotwani, Aneeta; Qureshi, Shahida; Kabir, Furqan; Aziz, Fatima; Memon, Naveed Masood; et al.
Summary: Background: Pakistan is currently facing the largest outbreak of ceftriaxone-resistant Salmonella enterica serotype Typhi described to date. Here we aimed to report the outbreak investigation done in Hyderabad, Pakistan, and identify disease risk factors. Methods: We did an age-matched case-control (1:4) study, in which cases of ceftriaxone-resistant S Typhi were identified from active sentinal sites (three hospitals in Hyderabad, Pakistan), community, and laboratory-based surveillance. Ceftriaxone-resistant S Typhi infection (ie, resistance to ampicillin, chloramphenicol, co-trimoxazole, fluoroquinole, and ceftriaxone) was confirmed using blood culture. Healthy participants (controls) were enrolled for the first 200 people (cases) with ceftriaxone-resistant S Typhi. A structured questionnaire was administered to identify exposures 4 weeks before the illness (cases) or enrolment (controls). Cases were included if written informed consent was provided. Four controls were selected from the same community as the corresponding case, matched on age, being healthy at the time of enrolment, and with no febrile illness in the 4 weeks before enrolment. Samples of drinking water from households and community water sources (ie, hand pumps or taps in common areas outside households) were collected for testing. Conditional logistic regression analysis was used to assess the risk factors for ceftriaxone-resistant S Typhi outbreak in Hyderabad. Findings: Between Nov 30, 2016, and Dec 30, 2017, 486 people with ceftriaxone-resistant S Typhi were identified from Hyderabad. Of the 486 cases, 296 (61%) were male and 447 (92%) were aged 15 years or younger. Several factors were significantly associated with acquisition of ceftriaxone-resistant S Typhi, including male sex (adjusted odds ratio [aOR] 1·53, 95% CI 1·06–2·21), eating outside of the house (aOR 1·48, 1·01–2·19), exposure to a patient with S Typhi infection (aOR 3·81, 2·21–6·83), and a history of antimicrobial use (aOR 4·25, 2·53–7·13). Nine (69%) of 13 water samples taken from the households of people with ceftriaxone-resistant S Typhi infection were positive for Escherichia coli, indicating faecal contamination. S Typhi DNA was detected in 12 (22%) of 55 water samples from community water sources. Geospatial mapping showed clustering of cases around sewerage lines. Interpretation: Hyderabad faces the largest reported outbreak of ceftriaxone-resistant S Typhi. The outbreak is suspected to be attributed to the contaminated drinking water, especially the mixing of sewage with drinking water. The risk of ceftriaxone-resistant S Typhi infection is increased among children aged 15 years and younger, male individuals, and those eating outside the house. Vaccination and chlorination of water are recommended for the containment of the outbreak. Funding: None.